Dynamic Response of Bridge Decks to Steady State Wind Loads: A CFD Approach - Supriyadi, Bambang; Triwiyono, Andreas; Farhan, Muhamad (Universitas Ibn Khaldun Bogor, 2026)
Indonesia, as an archipelago nation located on the equator, is affected by alternating Asian and Australian monsoon systems throughout the year. The east monsoon spans from April to September, while the west monsoon occurs from October to March. In Samarinda, prevailing southern winds lead to significant fluctuations in speed and direction, impacting the stability of bridge structures. Extreme wind events pose risks to suspension bridges through aerodynamic phenomena like flutter, galloping, and vortex shedding, which impose substantial dynamic loads on the structure.This study focuses on analyzing the dynamic response of bridge decks under steady state wind loads. Daily wind data collected from January 2023 to January 2024 revealed wind speeds of 3, 4, and 5 m/s, with extreme speeds reaching 14 and 20 m/s. Steady state simulations were conducted using the simpleFoam solver in Simscale at these speeds, along with the critical velocity of 8.764 m/s derived from the bridge deck's cross-section. The simulation results provided valuable insights into pressure distributions and lateral displacement on the deck.Findings indicate that lateral displacement at a wind speed of 20 m/s reaches 1.235 m, which exceeds design limits and highlights potential structural vulnerabilities. These results demonstrate the effectiveness of steady state CFD simulations in assessing wind-induced effects on bridge structures and underline the importance of mitigation strategies to ensure stability.